Safety of histamine-2 receptor blockers in hospitalized VLBW infants. (August 2016) - Romaine, Andrew; Ye, Daniel; Ao, Zachary; Fang, Francia; Johnson, Octavious; Blake, Taylor; Benjamin, Daniel K.; Cotten, C. Michael; Testoni, Daniela; Clark, Reese H.; Chu, Vivian H.; Smith, P. Brian; et al.
Abstract: Background: Histamine-2 receptor (H2 ) blockers are often used in very low birth weight infants despite lack of population specific efficacy and safety data. Aims: We sought to describe safety and temporal trends in histamine-2 receptor (H2 ) blocker use in hospitalized very low birth weight (VLBW) infants. Study design: We conducted a retrospective cohort study using a clinical database populated by an electronic health record shared by 348 neonatal intensive care units in the United States. Subjects: We included all VLBW infants without major congenital anomalies. Outcome measures: We used multivariable logistic regression with generalizing estimating equations to evaluate the association between days of H2 blocker exposure and risk of: 1) death or necrotizing enterocolitis (NEC); 2) death or sepsis; and 3) death, NEC, or sepsis. Results: Of 127, 707 infants, 20, 288 (16%) were exposed to H2 blockers for a total of 6, 422, 352 days. Median gestational age for infants exposed to H2 blockers was 27 weeks (25th 75th percentile 26, 29). H2 blocker use decreased from 18% of infants in 1997 to 8% in 2012 (p < 0.001). On multivariable analysis, infants were at increased risk of the combined outcome of death, NEC, or sepsis on days exposed to H2 blockers (odds ratio = 1.14) (95% confidence interval 1.08, 1.19). Conclusions: H2 blocker use is associated with increased risk of the combined outcome of death, NEC, or sepsis in hospitalized VLBW infants. Highlights: Using a multicenter electronic health record based clinical database, we characterized histamine-2 receptor (H2 ) blocker use in very low birth weight (VLBW) infants. We found that despite decreasing use over time, VLBW infants frequently remained exposed to H2 blockers and that exposure was associated with increased morbidity and mortality.